Magnetismo de baixa dimensão no Fe1-xCuxNbO4 - Evaristo, Diego da Silva (2023)
In the present work, iron and copper niobates (Fe1xCuxNbO4 with x = 0 - 0.15 and 0.25) were prepared by the modified solid state method and characterized by diffraction of X-rays (XRD), scanning electron microscopy (SEM/EDX), Mössbauer spectroscopy (EM), temperature-dependent (10 - 1000 K) and magnetic field Raman spectroscopy (ER), magnetic measurements as a function of temperature (M-T, 1.8 - 1000 K) and magnetic field (M-H) and measurements of AC magnetic susceptibility as a function of frequency and DC field. The results (DRXs and ER) confirm the phase (mFeNbO4), as well as the local influences caused by the insertion of Cu ions. SEM suggests a non-uniform particle size distribution with a mean diameter of 1.62 µm. Magnetic analyzes (M - H and M - T) confirmed that the FeNbO4 structure presents an antiferromagnetic (AFM) ordering state, with temperature TN ~36.81 K and revealed an antiferromagnetic-ferrimagnetic transition (AFM-FIM) due to the replacement of Fe3+ ions by Cu2+ ions in Fe1-xCuxNbO4 (x > 0.05), which remains above ambient temperature. The analysis by study of the magnetocaloric effect (EMC), through the analysis of the temperature-dependent variation of magnetic entropy (SM) in different magnetic fields (1 to 7 T), confirms the transition of the magnetic order from AFM to FIM, with a transition temperature of T´N = 38 K, for sample Fe0.75Cu0.25NbO4. AC magnetic susceptibility measurements (Xac(T,f ) and Xac(T,f ,H)), show that, at low temperatures, the insertion of Cu2+ causes an increase in magnetic anisotropy and, in the absence of long range order (LRO) it promotes slow magnetic relaxation processes, between 52 and 163 K, which strongly resemble the behavior of a single-chain magnet (SCM). The magnetic studies at high temperatures showed the magnetic transition FIM-PM (ferrimagnetic-paramagnetic) with TC = 908 K, through measurements of temperature-dependent magnetization (M-T) and evidenced by Raman spectroscopy dependent on temperature and field. We also report the direct observation of the magnetic excitation of two magnons and the couplings of magnons-phonons, spin-phonons in the FIM-PM magnetic transition region for Fe0.75Cu0.25NbO4, via temperature-dependent Raman spectroscopy.